The transcription cycle of RNA polymerase II in living cells. - Kimura, H; Sugaya, K; Cook, P (2002)
RNA polymerase II transcribes most eukaryotic genes. Its catalytic subunit was tagged with green fluorescent protein and expressed in Chinese hamster cells bearing a mutation in the same subunit; it complemented the defect and so was functional. Photobleaching revealed two kinetic fractions of polymerase in living nuclei: approximately 75% moved rapidly, but approximately 25% was transiently immobile (association t1/2 approximately 20 min) and transcriptionally active, as incubation with 5,6-dichloro-1-beta-D-ribofuranosylbenzimidazole eliminated it. No immobile but inactive fraction was detected, providing little support for the existence of a stable holoenzyme, or the slow stepwise assembly of a preinitiation complex on promoters or the nuclear substructure. Actinomycin D decreased the rapidly moving fraction, suggesting that engaged polymerases stall at intercalated molecules while others initiate. When wild-type cells containing only the endogenous enzyme were incubated with [3H]uridine, nascent transcripts became saturated with tritium with similar kinetics (t1/2 approximately 14 min). These data are consistent with a polymerase being mobile for one half to five sixths of a transcription cycle, and rapid assembly into the preinitiation complex. Then, most expressed transcription units would spend significant times unassociated with engaged polymerases.